A study on disaster management practices for vulnerable rural communities in Bangladesh - Mahalder, Bidyuth K; Islam, Md Shahidul; Hossain, BM Rabby; Nabi, Farah Didul (Bangladesh Journal of Scientific Research, 2018)
The current disaster knowledge and practices of disaster affected rural people in Bangladesh were investigated. Both qualitative and quantitative data were collected using structured questionnaire from 216 rural households. About 83% of the respondents perceived knowledge that brings about an increase in household income followed by learning new skills that contribute to reduction in disaster vulnerabilities (75%) and knowledge that helps in the decision making process (67%). A total of 91% of respondents, irrespective of literacy, are practicing tacit or oral knowledge sharing in their day to day lives. The sample respondents acquired disaster knowledge from different sources, including neighbors and relatives (82%), social workers (50%), mass media (45%), religious institutions (38%) and the village markets (32%). For those that received their knowledge from the village market, the information is mainly gathered by the literate people (37%) as opposed to those that are illiterate (26%). In updating acquired knowledge, 76% respondents validated through self observations and 58% by consultation and communication with family members or neighbors. Interestingly, more than 74% respondents reported that an inadequate financial resource is an important barrier to gaining improved knowledge on disaster management in rural areas. About 69% of the respondents stated that the early warning messages provided by various agencies are ‘very useful’, whereas 23% believed them to be ‘useful’ and 8% as ‘partially useful’. Posters, booklets and leaflets were identified as the most available and important disaster knowledge materials (82%). The study results suggested that the establishment of the rural information and knowledge centre and an easily understandable forecasting system would be very useful to improve the disaster knowledge for the rural poor. Bangladesh J. Sci. Res. 30(1&2): 55-67, December-2017